Spherical silica composite particles and method for producing the same
Patent Information
- Application Number
- JP2023139743
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明によれば、比誘電率が低く、樹脂への充填性に優れた球状シリカ複合粒子及びその製造方法が提供される。 本発明の球状シリカ複合粒子は、積層板等を低誘電率化させるシリカ粒子フィラーとして好適に用いることができる。
Smart Images

Figure 2025033779000001
Abstract
Description
[Technical field]
[0001] The present invention relates to spherical silica composite particles suitable for applications such as electronic wiring boards, and a method for producing the same. [Background technology]
[0002] It is known that silica particle fillers are blended with resin materials for sealing materials and copper-clad laminates (hereinafter referred to as laminates, etc.) used in electronic wiring boards in order to improve heat dissipation and reduce thermal expansion. In recent years, with the trend toward higher functionality and smaller size of electronic device packages, there is a demand for laminates and the like to have improved insulation properties and even lower thermal expansion. In response, various improvements have been investigated not only for resin materials but also for silica particle fillers.
[0003] As silica particles used as a filler, the following are generally known. For example, there are spherical silica particles obtained by a deflagration method in which silicon powder is reacted with oxygen (see Patent Document 1), and hollow silica particles obtained by coating calcium carbonate with silica and then dissolving the calcium carbonate (see Patent Document 2). Other examples include a method of producing colloidal silica by forming an aqueous silica sol from an alkali metal silicate solution (see Patent Document 3), and wet silica produced by a sol-gel method using a method such as hydrolysis and polycondensation of tetraalkoxysilane. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4958404 [Patent Document 2] JP 2014-125400 A [Patent Document 3] Patent No. 5920976 Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the spherical silica particles produced by the deflagration method are inexpensive, they are amorphous particles and it is difficult to control the particle size, so that it is difficult to say that they are suitable as a filler for reducing the dielectric constant of laminates and the like. In addition, it is difficult to obtain uniform hollow silica particles, resulting in variations in the filling properties as a filler. Furthermore, because the particles are hollow, it is difficult to achieve uniform physical properties such as the mechanical strength of laminates, etc. In addition, conventional wet-process silica is easier to obtain as particles having a smaller and more uniform particle size than those obtained by the deflagration method, and can be used as a filler to achieve high loading, but it cannot be said that this is sufficient to reduce the dielectric constant of laminates, etc.
[0006] Under these circumstances, there is a demand for a silica particle filler that is suitable for lowering the dielectric constant of laminates and the like.
[0007] An object of the present invention is to provide spherical silica composite particles which have a low relative dielectric constant, excellent filling properties in resin, and are suitable as a silica particle filler for lowering the dielectric constant of laminates and the like, and a method for producing the same. [Means for solving the problem]
[0008] The present invention is based on the discovery that certain spherical silica composite particles containing carbon obtained by a sol-gel method are suitable for lowering the dielectric constant of laminates and the like.
[0009] The present invention provides the following means. [1] Spherical silica composite particles having a carbon content of 1.0 to 50.0 mass% and a sphericity of more than 0.95. [2] The spherical silica composite particles of [1], having a BET specific surface area of 5.0 times or less the theoretical specific surface area. [3] Spherical silica composite particles according to [1] or [2], in which the 10% cumulative volume particle diameter D10, the 50% cumulative volume particle diameter D50, and the 90% cumulative volume particle diameter D90 satisfy the relationship of the following formula (I): (D90-D10) / D50≦0.50 (I) [4] Spherical silica composite particles according to any one of [1] to [3], having a cumulative volume 50% particle diameter D50 of 50 μm or less. [5] A spherical silica composite particle according to any one of [1] to [4], having carbon atoms inside the particle. [6] A spherical silica composite particle according to any of [1] to [5], which is wet silica.
[0010] [7] A method for producing spherical silica composite particles according to any one of [1] to [6], comprising hydrolyzing and polycondensing a trifunctional alkoxysilane represented by the following formula (1) in an aqueous medium to obtain the spherical silica composite particles. R 1 Si(OR 2 )3(1) (In formula (1), R 1 is an alkyl group having 1 to 4 carbon atoms. 2 are each independently a hydrolyzable group. [8] The method for producing spherical silica composite particles according to [7], wherein the aqueous medium is water. Effect of the Invention
[0011] According to the present invention, there are provided spherical silica composite particles having a low relative dielectric constant and excellent fillability into resin, and a method for producing the same. The spherical silica composite particles of the present invention can be suitably used as a silica particle filler for lowering the dielectric constant of laminates and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The definitions and meanings of the terms and expressions used in this specification are given below. The silica composite particles refer to particles that contain carbon atoms and have a siloxane bond as the main skeleton. The preferred numerical ranges can be formed by any combination of the preferred lower limit values and upper limit values. The carbon content is a value measured by a combustion infrared absorption method, specifically, by the method described in the examples. The sphericity is a value calculated by dividing the difference between the maximum and minimum diameters of 500 particles in an image (magnification: 5000 times) observed with a scanning electron microscope (SEM) by 2. Specifically, it can be determined by the method described in the Examples. The BET specific surface area is a value measured by a flow method (one-point method) using a mixed gas of 30 volume % nitrogen and 70 volume % helium as an adsorption gas. Specifically, it is determined by the method described in the Examples. The theoretical specific surface area is calculated by dividing the particle diameter d [μm] of a spherical particle by the cumulative volume 50% particle diameter D50 (described later) and the dry density ρ [g / cm 3 ], the value [m 2 The dry density is a density based on volume measurement using helium gas, and is specifically measured by the device described in the Examples. The 10% cumulative volume particle diameter D10, the 50% cumulative volume particle diameter D50, and the 90% cumulative volume particle diameter D90 are values obtained from the volumetric particle size distribution of 500 particles in an image observed by SEM (magnification: 5000 times). Specifically, they are obtained by the method described in the Examples.
[0013] [Spherical silica composite particles] The spherical silica composite particles (hereinafter simply referred to as particles) according to an embodiment of the present invention (hereinafter also referred to as this embodiment) have a carbon content of 1.0 to 50.0 mass % and a sphericity of more than 0.95. In this way, spherical silica composite particles containing a predetermined amount of carbon components and having high sphericity have a low relative dielectric constant and excellent filling ability into resins, and can be suitably used as a silica particle filler for achieving a low dielectric constant of laminates and the like.
[0014] The carbon content of the spherical silica composite particles is 1.0 to 50.0% by mass, preferably 5.0 to 45.0% by mass, and more preferably 15.0 to 40.0% by mass. If the carbon content of the spherical silica composite particles is 1.0 mass % or more, they have a sufficiently low relative dielectric constant, and if the carbon content is 50.0 mass % or less, they can function as a filler to provide laminates and the like with a sufficiently low thermal expansion coefficient.
[0015] The spherical silica composite particles preferably have a low relative dielectric constant and are homogeneous, and from the viewpoint of improving the filling property in the resin without surface treatment, it is preferable that the carbon component is uniformly present in the particles. Therefore, it is preferable that the spherical silica composite particles have carbon atoms inside the particles. The carbon atoms may be present on the outer surface of the particles, but it is preferable that they are also present inside the particles.
[0016] The sphericity of the spherical silica composite particles is more than 0.95, and preferably 0.96 or more. The closer the sphericity is to 1, the closer the shape is to a perfect sphere, and in the present invention, the closer the shape is to a perfect sphere, that is, the closer the sphericity is to 1, is preferable. When the sphericity is greater than 0.95, the spherical silica composite particles have excellent fillability in resin and tend to have a low relative dielectric constant.
[0017] From the viewpoint of providing good packing properties due to appropriate compatibility with resins, the spherical silica composite particles preferably have a BET specific surface area of 5.0 times or less, more preferably 2.1 to 4.8 times, and even more preferably 2.5 to 4.5 times, the theoretical specific surface area.
[0018] It is preferable that the spherical silica composite particles have a 10% cumulative volume particle diameter D10, a 50% cumulative volume particle diameter D50, and a 90% cumulative volume particle diameter D90 that satisfy the relationship of the following formula (I). (D90-D10) / D50≦0.50 (I)
[0019] The left side of formula (I) is an index of the particle size distribution of the spherical silica composite particles, and the smaller the value, the narrower the particle size distribution width. When the value of the left side is 0.50 or less, that is, when the relationship of formula (I) is satisfied, the particle has an appropriately narrow particle size distribution width, a relatively uniform particle size, and tends to have good fillability in resin. The value of the left side is more preferably 0.10 to 0.50, and even more preferably 0.20 to 0.49.
[0020] From the viewpoint of good filling properties of the particles in the resin, D50 is preferably 50 μm or less, more preferably 20 μm or less, and further preferably 0.1 to 5 μm. D10 and D90 are not particularly limited as long as they satisfy the relationship of formula (I).
[0021] The spherical silica composite particles are preferably wet silica. For example, if the wet silica is obtained by a sol-gel method or the like, it is easy to obtain spherical silica composite particles having the above-mentioned physical properties. Although the specific manufacturing method of the wet silica is not particularly limited, the wet silica can be suitably manufactured according to the manufacturing method of the present embodiment described later.
[0022] The spherical silica composite particles of this embodiment can be suitably used as a silica particle filler to be blended with a resin in a laminate plate or the like used in an electronic wiring board. The resin to be mixed with the spherical silica composite particles is not particularly limited, and may be a thermosetting resin, a thermoplastic resin, or a composite resin thereof. From the viewpoint of heat resistance, a thermosetting resin is preferred.
[0023] Examples of thermosetting resins include silicone resins (including silicone rubber), epoxy resins, phenolic resins, bismaleimide resins, cyanate resins, urethane resins, (meth)acrylic resins, vinyl ester resins, unsaturated polyester resins, and polyvinyl acetal resins. A curing agent, a curing accelerator, and the like may be added to the thermosetting resin. Among these, silicone resins are preferred from the viewpoint of good flexibility and adhesion. Also, epoxy resins are preferred from the viewpoints of heat resistance, adhesion, insulation, and the like.
[0024] Examples of silicone resins include addition reaction curing silicone resins, condensation reaction curing silicone resins, organic peroxide curing silicone resins, etc. In laminates and the like, from the viewpoint of excellent flexibility and adhesion, addition reaction curing liquid silicone resins are preferred because they are less likely to produce bubbles due to by-products, etc.
[0025] Examples of epoxy resins include bifunctional glycidyl ether type epoxy resins such as bisphenol A type, bisphenol F type, bisphenol S type, hydrogenated bisphenol A type, and biphenyl type; glycidyl ester type epoxy resins such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester; linear aliphatic epoxy resins such as epoxidized polybutadiene and epoxidized soybean oil; heterocyclic epoxy resins such as triglycidyl isocyanurate; N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N, Examples of epoxy resins include glycidylamine type epoxy resins such as N',N'-tetraglycidyl-1,3-benzenedi(methanamine), 4-(glycidyloxy)-N,N-diglycidylaniline, and 3-(glycidyloxy)-N,N-diglycidylaniline; phenol novolac type epoxy resins; cresol novolac type epoxy resins; biphenyl aralkyl type epoxy resins; naphthalene aralkyl type epoxy resins; and polyfunctional glycidyl ether type epoxy resins with three or more functional groups, such as tetrafunctional naphthalene type epoxy resins and triphenylmethane type epoxy resins.
[0026] The amount of the spherical silica composite particles to be mixed with the resin can be appropriately adjusted depending on the specific dielectric constant and heat resistance required for the laminate or the like. The spherical silica composite particles of this embodiment have good filling properties, and even when mixed with a resin in the same amount or more, a molded product having an integral shape can be obtained, and it is possible to effectively reduce the dielectric constant of laminates, etc.
[0027] [Method of manufacturing spherical silica composite particles] The method for producing spherical silica composite particles of the present embodiment involves hydrolyzing and polycondensing a trifunctional alkoxysilane represented by the following formula (1) in an aqueous medium to obtain the spherical silica composite particles. R 1 Si(OR 2 )3(1) (In formula (1), R 1 is an alkyl group having 1 to 4 carbon atoms. 2 are each independently a hydrolyzable group.
[0028] The raw material alkoxysilane used in the production of silica particles by the conventional sol-gel method is generally a tetrafunctional alkoxysilane having four alkoxy groups, such as tetraethoxysilane. In contrast, in the production method of the present embodiment, a trifunctional alkoxysilane is used as the raw material, as shown in formula (1). Therefore, R bonded to the silicon atom is formed by hydrolysis and polycondensation of the raw material alkoxysilane. 1 remains bonded to silicon atoms in the synthesized silica particles, and R 1 Thus, spherical silica composite particles containing carbon atoms derived from the carbon nanotube are obtained. In such wet silica by the sol-gel method, R 1 It is presumed that the carbon atoms derived from the alkoxysilane are uniformly present on the outer surface and inside of the spherical silica composite particles. In addition, when the raw material alkoxysilane is bifunctional, it is difficult to obtain the spherical silica composite particles of the present embodiment having the desired shape, i.e., high sphericity, predetermined physical properties such as particle size, etc. However, during the hydrolysis and polycondensation of the trifunctional alkoxysilane represented by formula (1), other silane compounds such as bifunctional alkoxysilanes such as dimethyldiethoxysilane may be copolymerized.
[0029] In formula (1), R 1 In order to obtain spherical silica composite particles with an appropriate carbon content, the alkyl group is an alkyl group having 1 to 4 carbon atoms, and preferably an alkyl group having 1 to 3 carbon atoms. By having 4 or less carbon atoms, the synthesized silica composite particles are less likely to fuse to each other, making it easier to obtain spherical particles.
[0030] 3 ORs 2 are each independently a hydrolyzable group. 2 may be the same or different. OR 2 Since R is eliminated by hydrolysis, it does not remain in the synthesized spherical silica composite particles and does not affect the components contained in the particles. 2 is not particularly limited, but in consideration of the reaction rate of hydrolysis, by-products, etc., it is preferable that the carbon chain is short, and it is preferably an alkyl group having 1 to 3 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms. That is, OR 2 is more preferably a methoxy group or an ethoxy group.
[0031] Preferable specific examples of the trifunctional alkoxysilane represented by formula (1) include methyltriethoxysilane, ethyltriethoxysilane, n-propyltriethoxysilane, etc. Commercially available products can be used as these compounds.
[0032] The hydrolysis and polycondensation of the trifunctional alkoxysilane are carried out in an aqueous medium. The aqueous medium is water or an organic solvent that is easily miscible with water. The aqueous medium may be one type alone or a mixture of two or more types. In the case of a mixture, a mixture of an organic solvent and water is preferred from the viewpoint of promoting the hydrolysis reaction. Examples of the organic solvent include alcohols such as methanol, ethanol, propanol, etc. The organic solvent is preferably the same type of alcohol as that generated from the leaving group after hydrolysis of the trifunctional alkoxysilane. When a mixture of an organic solvent and water is used as the aqueous medium, the R 1 In order to suppress fusion between the sites originating from the polymer and obtain particles with high sphericity, it is preferable that the molar ratio of the organic solvent to water is small, preferably 0.7 or less, more preferably 0.5 or less, and even more preferably 0.1 or less. From the viewpoints of ease of production of particles with high sphericity and production costs, it is more preferable that the aqueous medium is water alone.
[0033] From the viewpoint of efficient reaction progress, the amount of the aqueous medium in the reaction medium is preferably 5 to 200 times by mass, more preferably 10 to 150 times by mass, and further preferably 15 to 100 times by mass relative to the amount of the raw material trifunctional alkoxysilane.
[0034] The hydrolysis and polycondensation of the trifunctional alkoxysilane are preferably carried out in the presence of an alkali catalyst, such as ammonia, potassium hydroxide, sodium hydroxide, etc., and of these, ammonia is preferred. The hydrolysis and polycondensation in the manufacturing method of this embodiment can be carried out under the same reaction conditions as those of conventional hydrolysis and polycondensation using tetraalkoxysilane as a raw material. For example, in the presence of an ammonia catalyst, the raw material trifunctional alkoxysilane is dropped into an aqueous medium containing water, and the resulting sol is reacted to gel, and then dried to produce spherical silica composite particles. More specifically, the spherical silica composite particles can be produced by the method described in the examples.
[0035] The reaction temperature varies depending on the aqueous medium used, but is preferably 15 to 80° C., more preferably 20 to 75° C., and even more preferably 25 to 70° C., from the viewpoints of promoting the reaction and suppressing volatilization of the aqueous medium. From the viewpoint of sufficient progress of the reaction and production efficiency of the particles, the reaction time is preferably 1 to 48 hours, more preferably 2 to 42 hours, and further preferably 3 to 36 hours.
[0036] The reaction product is washed with an organic solvent such as alcohol, and then dried to obtain powdered spherical silica composite particles. Drying may be performed by heating from the viewpoint of drying efficiency, as long as the organic solvent is sufficiently volatilized and removed, but air drying at room temperature may be performed from the viewpoint of suppressing fusion between particles. EXAMPLES
[0037] Hereinafter, the present invention will be described in detail with reference to examples. However, the present invention is not limited to the following examples.
[0038] [Preparation of silica composite particle samples] Example 1 500 mL of 0.5 mol / L ammonia water was placed in a 1 L beaker and heated to 50°C while stirring with a stirrer (two blades, 300 rpm). 1 32.4 g of methyl group (carbon number 1) was added dropwise at 0.5 mL / min. After the addition was completed, the mixture was stirred for 24 hours while maintaining the temperature at 50°C, and then allowed to cool naturally. The contents of the beaker were centrifuged (4000 rpm for 5 minutes; the same applies below), after which the solid matter was recovered and dispersed in ethanol, and centrifuged again. This process was repeated five times to obtain an ethanol-dispersed slurry. The obtained slurry was poured into an aluminum tray and air-dried at room temperature (25°C) for at least 24 hours to obtain a silica composite particle sample.
[0039] Example 2 In Example 1, methyltriethoxysilane was replaced with n-propyltrimethoxysilane (R 1 A silica composite particle sample was obtained in the same manner as in Example 1, except that the alkyl group was changed to an n-propyl group (having 3 carbon atoms).
[0040] Example 3 A silica composite particle sample was obtained in the same manner as in Example 1, except that the 0.5 mol / L ammonia water was changed to a mixed solution of ethanol and water (ethanol / water molar ratio 0.5) with an ammonia concentration of 0.5 mL / L.
[0041] Comparative Example 1 In Example 1, methyltriethoxysilane was replaced with n-hexyltrimethoxysilane (R 1 The synthesis was attempted in the same manner as in Example 1, except that the group was changed to an n-hexyl group (having 6 carbon atoms), but a particulate sample could not be obtained.
[0042] Comparative Example 2 A silica composite particle sample was obtained in the same manner as in Example 1, except that the 0.5 mol / L ammonia water was changed to a mixed solution of ethanol and water (ethanol / water molar ratio 1.5) with an ammonia concentration of 0.5 mL / L. The particles obtained were of irregular shape and were fused together. The sphericity was measured by extracting measurable particles.
[0043] [Measurement and evaluation of particle samples] The following various measurements and evaluations were carried out for each sample obtained in the above examples and comparative examples. The results of these measurements and evaluations are shown in Table 1. For comparison and reference, the results of measurements and evaluations for commercially available silica particles ("Admafine (registered trademark) SO-25R", manufactured by Admatechs Co., Ltd.; manufacturing method: deflagration method) are shown in Table 1 as Comparative Example 3.
[0044] (Carbon content) The measurements were performed using a carbon / sulfur analyzer (EMIA-821FAW, Horiba, Ltd.) using the non-dispersive infrared absorption method with a tubular electric furnace.
[0045] (Sphericity) For 500 particles in the SEM observation image (magnification 5000x), the difference between the maximum and minimum diameters was divided by 2 using image processing software ("WinROOF", manufactured by Mitani Shoji Co., Ltd.) to calculate the sphericity.
[0046] (BET specific surface area) The measurement was performed using a fully automatic specific surface area measuring device (Macsorb (registered trademark) HM model-1210, manufactured by Mountec Co., Ltd.) by the BET flow method (one-point method, gas used: mixed gas of 30 volume % nitrogen and 70 volume % helium).
[0047] (dry density) The measurements were made using a dry automatic density meter ("AccuPic II 1340", manufactured by Shimadzu Corporation).
[0048] (10% cumulative volume particle size (D10), 50% cumulative volume particle size (D50) and 90% cumulative volume particle size (D90)) As in the measurement of sphericity, D10, D50, and D90 were obtained from the volumetric particle size distribution calculated by assuming the particles to be spheres through image processing of the SEM observation images. From these values, the value of (D90-D10) / D50 was calculated.
[0049] (Theoretical specific surface area) The D50 calculated above is regarded as the particle diameter d [μm] of the spherical particles, and the dry density ρ [g / cm 3 ] was calculated using the formula 6 / (ρ×d) (unit: m 2 In addition, the ratio (S1 / S0) of the BET specific surface area (S1) measured above to the theoretical specific surface area (S0) was calculated.
[0050] (Fillability) A silicone resin ("KE-1935-A / B", Shin-Etsu Chemical Co., Ltd.) and a particle sample were mixed in a mass ratio of 1 / 1 using a planetary centrifugal mixer ("Awatori Rentaro (registered trademark) ARE-310P", Thinky Corporation) at 2000 rpm for 90 seconds under reduced pressure, and this operation was repeated five times to prepare a resin composition. The obtained resin composition was sandwiched between PET films and formed into a film having a thickness of 0.5 mm using a rolling mill. In Table 1, when the resin composition could be molded into a sheet, the filling property was rated as A. When the resin composition did not come together and could not be molded into a sheet, the filling property was rated as B.
[0051] (Dielectric constant) The sheet-like molded product prepared in the above-mentioned evaluation of filling property was heated at 150° C. for 1 hour to obtain a cured product. The dielectric constant of the obtained cured product was measured using a dielectric constant measuring device (SPDR dielectric resonator, manufactured by Agilent Technologies, Inc.). In addition, the dielectric constant of the cured product of only the silicone resin was measured, and the dielectric constant of the particle sample was calculated from these measured values using the Maxwell-Garnett model.
[0052] [Table 1]
[0053] As can be seen from the results shown in Table 1, it was confirmed that the spherical silica composite particles (Examples) of this embodiment, which have a carbon content within a specified range and high sphericity, have good fillability into resin and a sufficiently low relative dielectric constant. From this, it can be said that the spherical silica composite particles of this embodiment can be suitably used as a silica particle filler that reduces the dielectric constant of laminates and the like.
Claims
1. The spherical silica composite particles have a carbon content of 1.0 to 50.0 mass % and a sphericity of more than 0.
95.
2. 2. The spherical silica composite particles according to claim 1, having a BET specific surface area of 5.0 times or less the theoretical specific surface area.
3. 3. The spherical silica composite particles according to claim 1, wherein the cumulative volume 10% particle diameter D10, the cumulative volume 50% particle diameter D50 and the cumulative volume 90% particle diameter D90 satisfy the relationship of the following formula (I). (D90-D10) / D50≦0.50 (I)
4. 3. The spherical silica composite particles according to claim 1, having a cumulative volume 50% particle diameter D50 of 50 μm or less.
5. 3. The spherical silica composite particle according to claim 1, having carbon atoms inside the particle.
6. 3. The spherical silica composite particle according to claim 1 or 2, which is wet silica.
7. A method for producing the spherical silica composite particles according to claim 1 or 2, A method for producing spherical silica composite particles, comprising hydrolyzing and polycondensing a trifunctional alkoxysilane represented by the following formula (1) in an aqueous medium to obtain the spherical silica composite particles: R 1 Si(OR 2 ) 3 (1) (In formula (1), R 1 is an alkyl group having 1 to 4 carbon atoms. 2 are each independently a hydrolyzable group.
8. The method for producing spherical silica composite particles according to claim 7 , wherein the aqueous medium is water.
Citation Information
Patent Citations
JP1974058404A
Connecting terminal
JP1984020976A
Method of producing spherical hollow silica particles
JP2014125400A